Pengaruh Profitabilitas, Leverage, Likuiditas, Dan Ukuran Perusahaan Terhadap Pengungkapan CSR - Yurika, Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This research aims to determine the effect of profitability, leverage, likuidity, and firm size on disclosure of corporate social responsibility (CSR). The population used in this research are manufacturing companies that have go public and listed on the Indonesia Stock Exchange (IDX) for the period 2015 to 2017. The samples were obtained by purposive sampling method so that 52 manufacturing companies were obtained duting the research period. Data analysis using the SPSS 23.00 program (Statistical Product and Services Solutions 23.00). The research model was analyzed after being free from classical assumptions. The results of the statistical analysis concluded that profitability, leverage, and liquidity was not significantly influence toward CSR disclosure, while the firm size has significantly influence toward CSR disclosure